2010
DOI: 10.1063/1.3367960
|View full text |Cite
|
Sign up to set email alerts
|

Entropy localization in magnetic compounds and thin-film nanostructures

Abstract: The effect of nanostructuring on the magnetic entropy of materials for room-temperature magnetic cooling is investigated by model calculations. The materials are structurally inhomogeneous with a large number of nonequivalent crystallographic sites. In the mean-field Heisenberg model, the entropy density is a unique function of the local magnetization so that the coupled set of nonlinear mean-field equations yields not only the magnetization but also the entropy density. Since most of the entropy is localized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
18
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…Recently, scientists have started doing research on the MCE properties of thin films, but only a few reports are currently available, [28][29][30][31][32][33] although in principle, such films will be easier to integrate into electronic structures for applications. 17 However, with the currently available magnetic materials, this high efficiency is only realized in high magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, scientists have started doing research on the MCE properties of thin films, but only a few reports are currently available, [28][29][30][31][32][33] although in principle, such films will be easier to integrate into electronic structures for applications. 17 However, with the currently available magnetic materials, this high efficiency is only realized in high magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the contemporary on-going research focuses on the giant MCE found in bulk rare-earth alloys. Recently, various nanotechnological approaches based on nanoparticles [5][6][7][8][9][10] and thin-film heterostructures [11][12][13] have been attempted to tailor microscopic magnetic parameters such as exchange and anisotropy for advanced magnetocaloric materials design. Discoveries of a giant MCE overcoming the magnetic limit for the isothermal entropy change reveal a mechanism based on coupling between structure and magnetism.…”
Section: Introductionmentioning
confidence: 99%
“…The nanoclusters have large "macrospins" J $ N and the entropy S of the clusters increases logarithmically with N, but the heat capacity scales with N (C $ N); therefore, the clusters cannot be large. 16,17 Embedding the nanoclusters into a interacting magnetic matrix effectively increases the quantum number J or the total spin of the composite material, which should enhance the isothermal entropy change. 17 This paper focuses on nanocomposites where Co nanoclusters, having an average cluster size of 2.0 nm, are embedded in a disordered-alloy matrix of Ni-Cu with compositions close to Ni 67 Cu 33 .…”
mentioning
confidence: 99%
“…[11][12][13] Also, recently, there has been a trend to use nanostructuring to tailor the magnetic properties, such as the anisotropy and exchange, to enhance the MCE of the materials by maximizing the isothermal entropy change in lower magnetic fields, suppressing hysteresis losses, and tuning the operation temperature to the desired range. [14][15][16][17][18] Researchers traditionally use magnetic phase transitions to enhance the isothermal entropy change and tune the operating temperature of MCE material, since, near transition temperatures, the effect of the applied magnetic field is increased due to the internal interatomic exchange interactions J ex . 1,3 First-order transitions can help if the phases involved have different entropies, which can produce large entropy changes.…”
mentioning
confidence: 99%
See 1 more Smart Citation